ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN INDUSTRI CAR FOOD DI KOTA AMBON - Selvenco Frans Tuasuun; Fransisca Soselissa (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2020)
This study aims to determine the factors that affect the income of the car food industry in Ambon City. The problem in this research is what kind of production and costs and how much is the level of car food income by using the descriptive method. Based on the results of the study, it is known that in Ambon city there are at least 12 industrial or car food industry businesses or mobile restaurants scattered in several places in the city, producing and selling several types of food and beverage menus at various prices. Income earned after all receipts are deducted by expenses as a profit from the car food business owner. The results of the regression analysis show that there is a close and influential relationship between the variables X1 (menu price / food), X2 (amount of sales) and X3 (cost of menu / food) on variable Y (income), with a value of R = 98.1%, and the value of R2 = 92.4%. Hypothesis testing uses the variance test and Ha is accepted at a 95% confidence level.